2012
DOI: 10.1111/j.1744-6155.2012.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in associations between parental problem drinking and early adolescents' Internet addiction

Abstract: Findings suggest that tailored interventions for the prevention of IA should consider gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 65 publications
2
26
0
4
Order By: Relevance
“…The majority of researchers (e.g., Jang & Ji, 2012; Lan & Lee, 2013) are in agreement that preventive interventions should focus mainly on children and adolescents. Children and adolescents are in their formative years, when values and standards develop, and they have the highest prevalence rates of Internet addiction (Šmahel et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of researchers (e.g., Jang & Ji, 2012; Lan & Lee, 2013) are in agreement that preventive interventions should focus mainly on children and adolescents. Children and adolescents are in their formative years, when values and standards develop, and they have the highest prevalence rates of Internet addiction (Šmahel et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Children and adolescents are in their formative years, when values and standards develop, and they have the highest prevalence rates of Internet addiction (Šmahel et al., 2009). For this reason, prevention programs should be implemented in the school environment, especially in elementary school settings that are often on the front line of the identification of potentially life-threatening behaviors (Jang & Ji, 2012; Lan & Lee, 2013). The South Korean government launched its plan for Internet addiction prevention and treatment with components starting with prevention interventions even with preschool children (Romano, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Internet addiction was associated with harmful use of alcohol among Taiwanese students (Yen, Ko, Yen, Chang, & Cheng, 2009). Parental problem drinking was also associated with Internet addiction through anxiety, depression, and aggression for boys and through family function and aggression for girls (Jang & Ji, 2012). …”
Section: Relationship Of Internet Addiction With Drug and Alcohol Usementioning
confidence: 99%
“…Man more often scored higher in Internet addiction scales (Jang & Ji, 2012;Stavropoulos, Alexandraki, & Motti-Stefanidi, 2013). Also, a study of German adolescents indicated gender differences in the patterns of Internet use and negative consequences of Internet use (Wartberg et al, 2014).…”
Section: Introductionmentioning
confidence: 97%